YOUTH EMPOWERMENT: CHALLENGES OF PROMOTING BUSINESS, EMPLOYMENT AND RECREATION - Wamalwa, Martin E. (IJRDO - Journal of Business Management, 2016)
Youth is an important stage both the individual person and society at large. To a society, youth are the potential “everything” that the society wants to be in future, while to the individual person, this is a transitional period from childhood to adulthood. This is a stage when the young are prepared for their future roles in the society. This preparation lies squarely with the society and individual person. As a society, the government of Kenya has been concerned with this issue, and for the last one decade, it has attempted to address it in various ways; among them the establishment of the Ministry of Youth and Sports, introduction of youth fund, creation of employment opportunities, and even including them in decision making processes. The Kenya Vision 2030 talks of promoting equity in power and resource distribution even to the youth and vulnerable groups, and improving livelihoods, and forming responsible, globally competitive and prosperous youth. Whereas we acknowledge that substantial steps have been made, experience, however, shows that the question of youth empowerment in Kenya still has a long way to be realized. Consequently, this paper discusses various challenges affecting the process of youth empowerment by promoting them in business, employment and recreation. It cites both personal and societal challenges and argues that attention to the challenges will speed up the process.